Barriers and incentives for choosing to specialise in mammography: Qualitative analysis. Issue 1 (February 2017) - Warren-Forward, H.M.; Taylor, J.
Abstract: Aim: There is a projected shortage of radiographers working in breast screening and this study aimed to examine comments from open response questions from a mixed methods survey of current diagnostic radiography students on their perceptions of working in mammography. Method: The survey asked three open ended questions: Justification of choice of modality in which they would want to specialise, why they believed there was a shortage of radiographers working in breast screening and any other comment about mammography. Results: Reasons given for specialising in any modality was interest, feature of a modality, amount of clinical exposure during the degree program, personal issues and career prospects. Few current diagnostic radiography students indicated that they would be interested in specialising in breast imaging. They considered there to be a shortage of radiographers as breast imaging was seen to be repetitive, high pressure, intimate and gender biased. Lack of education, clinical exposure, limited career prospects and low pay were also discussed. Conclusions: Increasing education to the modality during the degree, allowing males to be involved in breast imaging and promoting part-time work in mammography while also working in other modalities may alter the perception that mammography offers a limited career pathway. Highlights: Reasons to specialise in a modality include "interest", "clinical exposure" and "career prospect". Reasons not to specialise include "availability of modality" and "gender of radiographer". Repetitive nature of mammography was cited as the most common reason for shortage of radiographers. Restriction to female only radiographers was perceived to be a barrier. Mammography perceived to be high stress due to pressure on getting correct diagnosis.